Analisis Peramalan Permintaan Produk Calcium Carbonate Dengan Metode Forecasting di CV. Trijaya Abadi - Vivaldy Ferdiansyah Nugroho; Wahyudin Wahyudin (Peneliti.net, 2022)
CV. Trijaya Abadi is a company engaged in the lime material industry with goods sold, namely CaCO3 or Calcium Carbonate which is used as one of the main raw materials for various kinds of finished goods such as tires, paints, etc. Problems that exist in the CV. Trijaya Abadi is the imbalance in the number of orders in every first 6 months with the last 6 months. From the data obtained, the demand in the first 6 months and the last 6 months looks very much different, causing stock and demand to be unbalanced. The calculations that I use use the forecasting method to find out or forecast demand for the coming year, so that companies can estimate demand and make a balance between stock and demand.